Analisis Kualitas Pelayanan Terhadap Klaimen PT Jasa Raharja Cabang Sumatera Utara - afifa umami; Rahmi Syahriza (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2022)
This study aims to determine the quality of service provided by PT Jasa Raharja, North Sumatra Branch to the claimants or customers who are victims of road traffic accidents. The method used in this study is a qualitative method, which produces research in words and based on the results obtained in the field. This research was conducted at the North Sumatra Branch of the Jasa Raharja Office, which is located at Jl. Jendral Gatot Subroto No. 142 Medan. Types and sources of data used in this study are: Primary data and secondary data. Data collection techniques were carried out by means of observation, interviews and literature study. This study shows the results of the factors that hinder the quality of service, namely: many people do not understand the scope of guarantees borne by Jasa Raharja, communication to partners is not evenly distributed and external obstacles such as correspondence. The factor of the company is the lack of human resources that result in less effective and timely.